The reluctancy of Giatmara Perak ex-trainees in entrepreneurship / Ahmad Muzammir Muhammad and Rosman Ibrahim - Muhammad, Ahmad Muzammir; Ibrahim, Rosman (2008)
GIATMARA is one of the learning institutions under the Ministry of Entrepreneur and Cooperative Development (MeCD) which conduct skill training among the bumiputras. The MARA council which is an agency under the respective ministry has set up GIATMARA Centre in every parliamentary constituencies throughout the country. The training programs conducted by GIATMARA are targeted to the youth and local community who lives around the centre. These programs are created based on modular training which is a hands-on and employable skills that are currently in demand and it is provided FREE OF CHARGE. The duration of the program varies between 6 to 12 months. For the study purpose, the questionnaires have been distributed to eighty of GIATMARA Perak ex-trainees at random to obtain primary data. There are currently twenty three GIATMARA in Perak. From the eighty questionnaires distributed, only fifty were returned and the results are shown in forms of tablets and figures. All the data obtained in this study were gathered and analyzed using Statistical Package for Social Science (SPSS Version 12) and Microsoft Excel 2007. The researcher has conclude that the ex-trainees of GIATMARA Perak do not involved in entrepreneurship mainly due to initial capital. We have given some of our recommendations to GIATMARA Perak Centre on how to encourage the ex-trainees to be an entrepreneur.